Electrochemotherapy, Electrogenetherapy, and Transdermal Drug Delivery
DOI: 10.1385/1-59259-080-2:157
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and Ex Vivo Gene Delivery to Cells by Electroporation

Abstract: Electroporation generally refers to the technique of permeabilizing cell membranes by applying a short and intense electric pulse across a cell, such that the barrier function of the membrane is instantaneously compromised. During such time, genetic materials may travel across the membrane. For a successful gene transfer process, the barrier function of the cell membrane is rapidly restored, and the cell survives. The electrotransfection process thus comprises two steps. The first step is electroporation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Increased permeability of the cell membrane (indicated by dye uptake) occurs progressively longer after pulse application as the pulse duration shortens, and this temporal separation from the pulse application suggests that the membrane permeability effects are more likely due to alterations of cellular function rather than direct effects on surface membrane structure. The increase in cell size seen with pulses longer than 60 ns likely represents colloid osmotic swelling of cells in physiologic buffer, and as such, would be typical of electroporation with delayed resealing of the pores (Hui and Li, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Increased permeability of the cell membrane (indicated by dye uptake) occurs progressively longer after pulse application as the pulse duration shortens, and this temporal separation from the pulse application suggests that the membrane permeability effects are more likely due to alterations of cellular function rather than direct effects on surface membrane structure. The increase in cell size seen with pulses longer than 60 ns likely represents colloid osmotic swelling of cells in physiologic buffer, and as such, would be typical of electroporation with delayed resealing of the pores (Hui and Li, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cells can survive up to 50% volume increase and still recover 429,430,435,437,445,449 . Above that, the risk of instant death from bursting becomes imminent 450 . It is known that swelling activates specific stress signaling events 451 and is a classic hallmark associated with necrotic cell death 452,453 .…”
Section: Membrane Disruption-mediated Delivery: Background Conceptsmentioning
confidence: 99%
“…In addition, it is expected that electric pulses will act to porate cells in vivo, leading to increased cellular uptake of the photosensitizer. A number of studies have demonstrated that electroporation (cell electropermeabilization, electrochemotherapy) is an important development for the in vitro (51) or in vivo (52,53) cellular delivery of a number of molecules. Because ALA–PDT relies on the intracellular conversion of ALA to PpIX, this is particularly critical.…”
Section: Discussionmentioning
confidence: 99%